Study of the fertility of a carbonate red brown soil in a biomass bank with Cenchrus purpureus cv. CUBA CT-115 of ten exploitation years - Crespo López, G.; Cabrera Carcedo, E. A.; Díaz García, V. J. (Cuban Journal of Agricultural Science, 2018)
The objective of this experiment was to research, between 2013- 2015, the effect of biomass bank technology on soil fertility and on some morphological indicators of Cenchrus purpureus cv. Cuba CT-115, grazed for more than ten consecutive years in the genetic enterprise "Camilo Cienfuegos", in Pinar del Río province. It was found in the soil pH decrease (5.38 to 5.07, P <0.001), assimilable P2O5 (31.7 to 27.3 ppm; P <0.016), assimilable K2O (56.5 to 48.2 ppm; P <0.001), exchangeable Mg++ (1.10 to 0.82) cmol (+)/kg, P <0.001), base change capacity BCC (3.06 to 2.67 cmol (+)/kg, P <0.002) and cation-exchange capacity CEC (4.39 to 4.12 cmol (+)/kg; P <0.006), while organic matter OM increased (2.62 to 2.80 %; P <0.004) and interchangeable Ca ++, Na + and K + were not affected. In this case, the compaction significantly increased and the porosity and basal respiration decreased. The tillers/bunch indicator, determined in the rainy and dry seasons of 2015, showed a lower value (P <0.0001) in the dry season (10.70), which coincided with the lower value of the grass yield at that season of the year. The biomass of grass roots was higher in the depth of 15 - 30 cm of the soil (1.01 g/cylinder), in comparison with the superficial layer of 0 - 10 cm (0.54 g/ cylinder). However, in the area occupied by the biomass bank, in 2015 acceptable values in the grass morphological indicators, the macrofauna activity (especially earthworms) and the root biomass were found. It is concluded that this soil showed low resilience power, with significant decrease of pH and P, K and Mg contents in the bank that has ten years of uninterrupted grazing. This decrease in the indicators of soil fertility was also reflected in the decrease of CP, P and Ca contents, as well as in the CT-115 digestibility. These results warn about the need to supplement the animals that grazed in this bank with sources of protein, phosphorus and calcium to achieve the right balance in their diets. Key words: resilience, grazing, dairy unit, biomass.